Interpretation Struggles on Holy Place for Pura Uluwatu in Desa Adat Pecatu, South Kuta, Badung - Arniati, Ida Ayu (International Research Journal of Management, IT & Social Sciences, 2017)
The present study was intended to learn about the interpretation struggles that occurred around Bhisama Kesucian Pura that were established into Bali Provincial Regulation No. 16, in 2009 on Spatial Planning of Bali Province 2009-2029 (hereinafter referred to as Regional Regulation of RTRW Bali Provincial 16/2009) specifically for Pura Uluwatu area. This regulation raised the pros and cons between the society components. Interpretation struggles occurred due to there was no support and reject radius Area of holy place for Pura Uluwatu. There were two issues to be discussed in this paper, the first the cause of the struggle over the interpretation of the Holy Places Area at Pura Uluwatu, secondly the implications of interpretations struggle itself on the religious life, social and cultural.